Timing of delivery in women with diabetes: A population‐based study. (8th December 2019) - Metcalfe, Amy; Hutcheon, Jennifer A.; Sabr, Yasser; Lyons, Janet; Burrows, Jason; Donovan, Lois E.; Joseph, K. S.
Abstract: Introduction: Women with diabetes, and their infants, have an increased risk of adverse events due to excess fetal growth. Earlier delivery, when fetuses are smaller, may reduce these risks. This study aimed to evaluate the week‐specific risks of maternal and neonatal morbidity/mortality to assist with obstetrical decision making. Material and methods: In this population‐based cohort study, women with type 1 diabetes (n = 5889), type 2 diabetes (n = 9422) and gestational diabetes (n = 138 917) and a comparison group without diabetes (n = 2 553 243) who delivered a singleton infant at ≥36 completed weeks of gestation between 2004 and 2014 were identified from the Canadian Institute of Health Information Discharge Abstract Database. Multivariate logistic regression was used to determine the week‐specific rates of severe maternal and neonatal morbidity/mortality among women delivered iatrogenically vs those undergoing expectant management. Results: For all women, the absolute risk of severe maternal morbidity/mortality was low, typically impacting less than 1% of women, and there was no significant difference in gestational age‐specific severe maternal morbidity/mortality between iatrogenic delivery and expectant management among women with any form of diabetes. Among women with gestational diabetes, iatrogenic delivery was associated with an increased risk of neonatal morbidity/mortality compared with expectant management at 36 and 37 weeks' gestation (76.7 and 27.8 excess cases per 1000 deliveries, respectively) and a lower risk of neonatal morbidity/mortality at 38, 39 and 40 weeks' gestation (7.9, 27.3 and 15.9 fewer cases per 1000 deliveries, respectively). Increased risks of severe neonatal morbidity following iatrogenic delivery compared with expectant management were also observed for women with type 1 diabetes at 36 (98.3 excess cases per 1000 deliveries) and 37 weeks' gestation (44.5 excess cases per 1000 deliveries) and for women with type 2 diabetes at 36 weeks' gestation (77.9 excess cases per 1000 deliveries) weeks. Conclusions: The clinical decision regarding timing of delivery is complex and contingent on maternal‐fetal wellbeing, including adequate glycemic control. This study suggests that delivery at 38, 39 or 40 weeks' gestation may optimize neonatal outcomes among women with diabetes.